2018
DOI: 10.1002/14651858.cd001271.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Nurses as substitutes for doctors in primary care

Abstract: Background Current and expected problems such as ageing, increased prevalence of chronic conditions and multi‐morbidity, increased emphasis on healthy lifestyle and prevention, and substitution for care from hospitals by care provided in the community encourage countries worldwide to develop new models of primary care delivery. Owing to the fact that many tasks do not necessarily require the knowledge and skills of a doctor, interest in using nurses to expand the capacity of the primary care workf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
385
3
25

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(431 citation statements)
references
References 82 publications
18
385
3
25
Order By: Relevance
“…It is expected that NPs and PA substitute for ECPs more than RNs, given their level of education, qualifications, and authorizations (Ackermann & Kemle, ; Aigner, Drew, & Phipps, ). Nevertheless, RNs might sometimes substitute for physicians, as the work of physicians goes beyond reserved procedures; for example, patient assessment (Bedin et al, ; Laurant et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that NPs and PA substitute for ECPs more than RNs, given their level of education, qualifications, and authorizations (Ackermann & Kemle, ; Aigner, Drew, & Phipps, ). Nevertheless, RNs might sometimes substitute for physicians, as the work of physicians goes beyond reserved procedures; for example, patient assessment (Bedin et al, ; Laurant et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…• This paper deepens our understanding of traditional role concepts legal frameworks and reimbursement schemes as limiting barriers to a more integrated interprofessional collaboration which is required by current and future challenges in primary health care workload, decreases healthcare costs, improves satisfaction of both patient and healthcare provider (HCP) and provides equivalent or improved quality of care (Gielen, Dekker, Francke, Mistiaen, & Kroezen, 2014;Laurant et al, 2018;Martínez-González et al, 2014;Martínez-González, Tandjung, Djalali, & Rosemann, 2015;Parker, Maresco-Pennisi, Clifton, Shams, & Young, 2016;Riisgaard, Nexoe, Le, Sondergaard, & Ledderer, 2016;Watts & Lucatorto, 2014).…”
Section: Backg Rou N Dmentioning
confidence: 98%
“…Nevertheless, a better understanding of the potential contribution of nurses working in general practice is needed (Ball, Maben, & Griffiths, ). Research has demonstrated that this task shift generates similar or better health outcomes for a broad range of patient conditions, relieves the GP’s workload, decreases healthcare costs, improves satisfaction of both patient and healthcare provider (HCP) and provides equivalent or improved quality of care (Gielen, Dekker, Francke, Mistiaen, & Kroezen, ; Laurant et al, ; Martínez‐González et al, ; Martínez‐González, Tandjung, Djalali, & Rosemann, ; Parker, Maresco‐Pennisi, Clifton, Shams, & Young, ; Riisgaard, Nexoe, Le, Sondergaard, & Ledderer, ; Watts & Lucatorto, ). A recent overview of systematic reviews by Matthys Remmen, & Van Bogaert, () demonstrated that collaboration between physicians and nurses may have a positive impact on a range of patient outcomes and on a variety of pathologies when embedded within integrated interprofessional collaboration care models with adequately educated nurses (Matthys et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Advanced nursing practice has been found to be safe and effective (Laurant et al, 2018). However, it may lack acceptability and understanding, leading to underutilisation (Andregård & Jangland, 2015).…”
Section: Backg Rou N Dmentioning
confidence: 99%